Variation in the helical structure of native collagen. - Joseph P R O Orgel; Anton V Persikov; Olga Antipova (PLoS ONE)
The structure of collagen has been a matter of curiosity, investigation, and debate for the better part of a century. There has been a particularly productive period recently, during which much progress has been made in better describing all aspects of collagen structure. However, there remain some questions regarding its helical symmetry and its persistence within the triple-helix. Previous considerations of this symmetry have sometimes confused the picture by not fully recognizing that collagen structure is a highly complex and large hierarchical entity, and this affects and is effected by the super-coiled molecules that make it. Nevertheless, the symmetry question is not trite, but of some significance as it relates to extracellular matrix organization and cellular integration. The correlation between helical structure in the context of the molecular packing arrangement determines which parts of the amino acid sequence of the collagen fibril are buried or accessible to the extracellular matrix or the cell. In this study, we concentrate primarily on the triple-helical structure of fibrillar collagens I and II, the two most predominant types. By comparing X-ray diffraction data collected from type I and type II containing tissues, we point to evidence for a range of triple-helical symmetries being extant in the molecules native environment. The possible significance of helical instability, local helix dissociation and molecular packing of the triple-helices is discussed in the context of collagen's supramolecular organization, all of which must affect the symmetry of the collagen triple-helix.